2022
DOI: 10.1094/pdis-08-21-1601-re
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Phosphite Enhances the Antagonistic Capability of Bacillus amyloliquefaciens to Manage Tomato Bacterial Wilt

Abstract: Bacterial wilt caused by Ralstonia solanacearum is a distributed and worldwide soil-borne disease. The application of biocontrol microbes or agricultural chemicals has been widely used to manage tomato bacterial wilt. However, whether and how agricultural chemicals affect the antagonistic ability of biocontrol microbes is still unknown. Here, we combined potassium phosphite (K-Phite), an environmentally friendly agricultural chemical, and the biocontrol agent Bacillus amyloliquefaciens QPF8 (strain F8) to mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Phosphite is widely used to control P. cinnamomi damage in avocado orchards, and there is little data on how this might affect the soil microbiome. In tomato crops, phosphite has a beneficial effect; it suppresses Ralstonia solanacearum , and, when applied in conjunction with the biocontrol agent Bacillus amyloliquefaciens, it enhances its antagonistic activity (Su et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphite is widely used to control P. cinnamomi damage in avocado orchards, and there is little data on how this might affect the soil microbiome. In tomato crops, phosphite has a beneficial effect; it suppresses Ralstonia solanacearum , and, when applied in conjunction with the biocontrol agent Bacillus amyloliquefaciens, it enhances its antagonistic activity (Su et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the widespread use of fungicides has been increasingly limited because of the environmental risk and the emergence of fungicide-resistant strains of fungal pathogens [24]. Therefore, many studies have focused on combinations of fungicides and BCAs to effectively inhibit pathogens [15,[25][26][27]. However, few studies have shown the integrated management of banana Fusarium wilt by treatment with BCAs and fungicides.…”
Section: Discussionmentioning
confidence: 99%
“…Zakaria et al (2023) showed that the application of CBZ + SS + BS (a combination of the fungicide carbendazim, sodium silicate, and Bacillus subtilis) in farms signi cantly reduced the disease incidence by 16.07% and disease severity by 14.28% and enhanced the morphophysiological growth performance, with an average production yield of approximately 24.72 kg per fruit bunch [14]. The control e ciency of combined application of potassium phosphite with the antagonist bacterium B. amyloliquefaciens against tomato bacterial wilt was signi cantly greater than that of B. amyloliquefaciens F8 or K-Phite alone [15].…”
Section: Introductionmentioning
confidence: 99%